Psychotic experiences and psychiatric treatment utilization in Buenos Aires. (June 2020) - Oh, Hans; Koyanagi, Ai; DeVylder, Jordan E; Leiderman, Eduardo A
Objective: Psychotic experiences are associated with psychiatric treatment utilization, though findings have not been entirely consistent. Furthermore, it is unclear how psychotic experiences relate to specific types of psychiatric treatment, and whether mental illness moderates these associations. Methods: In total, 1, 036 adult residents of Buenos Aires were recruited through convenience sampling in public places. Multivariable logistic regression models examined the associations between psychotic experiences and psychiatric treatment, adjusted for age, sex and education. Analyses were then stratified by diagnosis of mental illness. Results: Approximately 17.95% ( N  = 186) of the sample reported at least one psychotic experience over the past week, about 22.39% ( N  = 232) of the sample was receiving some psychiatric or psychological treatment and 8.59% ( N  = 89) was receiving psychopharmacological treatment. In the total sample, psychotic experiences were associated with greater odds of being in psychiatric/psychological treatment (adjusted odds ratio (AOR): 1.52; 95% confidence interval (CI): 1.05–2.21) and psychopharmacological treatment (AOR: 2.49; 95% CI: 1.52–4.09), adjusted for age, sex and education. Mental illness did not moderate the association between psychotic experiences and psychiatric/psychological treatment, but did moderate the association between psychotic experiences and psychopharmacological treatment. Among people with mental disorders, psychotic experiences were associated with greater odds of receiving psychopharmacological treatment (AOR: 14.63; 95% CI: 1.73–123.45) versus people without mental disorders (AOR: 1.75; 95% CI: 0.98–3.15). Conclusion: Psychotic experiences are associated with psychiatric treatment utilization, particularly psychopharmacological treatment among people with a co-occurring mental illnesses. Translational research should explore the utility of psychosis screens in assessing need for medication or clinical responsiveness to medications.